No one is free, until everyone is free. How do actions for Palestine fit into the mission of the Hellenic Theatre/Drama & Education Network - Karaviti, Jenny (Education & Theatre, 2025)
Faithful to the principles of freedom, justice and the defence of human rights, the Hellenic Theatre/Drama & Education Network (TENet-Gr) aligns its Palestine-related activities with its goal of using theatre as a means of social transformation. Since 2010, TENet-Gr has participated in international campaigns, such as The Gaza Monologues by ASHTAR Theatre, and has developed educational and artistic programmes that amplify Palestinian voices. By establishing the “4 Colours” group, the organisation has reinforced its support for The Freedom Theatre and the Cultural Intifada movement. It has held, and continues to hold, public readings, online screenings and other solidarity events, and to collaborate with Palestinian artists. Through these initiatives, TENet-Gr promotes and supports cultural resistance to the settler-colonialist, apartheid and dehumanising regime that the Palestinian people have endured for over 70 years.